2001
DOI: 10.1046/j.1365-2567.2001.01252.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide protects cultured rheumatoid synovial cells from Fas‐induced apoptosis by inhibiting caspase‐3

Abstract: SUMMARYNitric oxide (NO) is elevated in the synovial¯uids and sera of patients with rheumatoid arthritis (RA) and is thought to be an important proin¯ammatory mediator in the rheumatoid synovium. To test the hypothesis that NO might modulate the apoptosis-inducing signal pathway, we investigated the effects of NO on rheumatoid synovial-cell apoptosis induced by Fas ligation with anti-Fas antibody. Pretreatment of synovial cells with the NO donor S-nitro-N-acetylpenicillamine (SNAP) prevented the Fas-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…We also found reduced processing of the large subunit of caspase-3 after SNP co-stimulation. Similar observations regarding the effects of NO-donors on CD95-dependent apoptosis were reported for a human T-cell line (Bernassola et al, 2001) and rheumatoid synovial cells (Migita et al, 2001). Consistent with the proposed model for CD95 mediated caspase-3 activation, the initial caspase-8 catalyzed cleavage of procaspase-3 yielded the p22 fragment of the large subunit (Daniel et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…We also found reduced processing of the large subunit of caspase-3 after SNP co-stimulation. Similar observations regarding the effects of NO-donors on CD95-dependent apoptosis were reported for a human T-cell line (Bernassola et al, 2001) and rheumatoid synovial cells (Migita et al, 2001). Consistent with the proposed model for CD95 mediated caspase-3 activation, the initial caspase-8 catalyzed cleavage of procaspase-3 yielded the p22 fragment of the large subunit (Daniel et al, 2001).…”
Section: Discussionsupporting
confidence: 80%
“…We compared the PsA patients with subjects affected by RA, an inflammatory disease, in which protein oxidation phenomena play an important pathogenic role. Furthermore, we compared PsA cases with patients affected by OA, commonly used as control by other authors (9,18,29), because of the evidence that oxidative stress does not seem to have a relevant role in this disease (30). The importance of oxidative stress in the joint compartment is confirmed by our finding that levels of SH groups in SF are inversely correlated with the number of WBC and percentage of PMN cells, which are both parameters of local inflammation in SF.…”
Section: Discussionmentioning
confidence: 59%
“…59 Consistent with this, rheumatoid arthritis is also associated with elevated serum and synovial fluid NO. 60 Migita et al 60 further suggested that synovial hyperplasia in rheumatoid arthritis results from resistance to Fas-mediated apoptosis in the presence of NO, as Fas-mediated apoptosis is suppressed by the addition of a NO donor to synovial cells. Their study further implicates NO in the inhibition of caspase-3 cleavage to its active form.…”
Section: Discussionmentioning
confidence: 99%